Major histocompatibility complex class‐II molecules promote targeting of human immunodeficiency virus type 1 virions in late endosomes by enhancing internalization of nascent particles from the plasma membrane. (12th December 2012) - Finzi, Andrés; Perlman, Mira; Bourgeois‐Daigneault, Marie‐Claude; Thibodeau, Jacques; Cohen, Éric A.
Summary Productive assembly of human immunodeficiency virus type 1 (HIV‐1) takes place, primarily, at the plasma membrane. However, depending on the cell types, a significant proportion of nascent virus particles are internalized and routed to late endosomes. We previously reported that expression of human leucocyte antigen (HLA)‐DR promoted a redistribution of Gag in late endosomes and an increased detection of mature virions in these compartments in HeLa and human embryonic kidney 293T model cell lines. Although this redistribution of Gag resulted in a marked decrease of HIV‐1 release, the underlying mechanism remained undefined. Here, we provide evidence that expression of HLA‐DR at the cell surface induces a redistribution of mature Gag products into late endosomes by enhancing nascent HIV‐1 particle internalization from the plasma membrane through a process that relies on the presence of intact HLA‐DR α and β‐chain cytosolic tails. These findings raise the possibility that major histocompatibility complex class‐II molecules might influence endocytic events at the plasma membrane and as a result promote endocytosis of progeny HIV‐1 particles.